Technologiczne uwarunkowania ekorozwoju - Parysek, Jerzy J. (Wydział Prawa i Administracji UAM, 1993)
Among the conceptions of socio-economic development earning currently greater credit, ecological approaches (sustainable development or eco-development) play an important role. The implementation of such formulas and their effective exploitation is possible solely after the fulfilment of certain conditions in various spheres of social life. An especially important role is played here by the technological determinants of eco-development. The study makes an attempt to prove that certain technological solutions, whose application may improve a broadly understood human life environment, are a key to eco-development. The technological progress will only be effective if (along with certain benefits for the environment) it brings about improvement in manufacturing processes, production costs reduction, improvement in an average man's living conditions and if it obtains political and social acceptance (cf. P. Larvor, 1991). The acceptance of pro-ecological technological solutions seems particularly important since it may bring about diversified results depending on time and space, results that may also affect to various extent the environment's quality and the population's living conditions. With regard to space, eco-development in its technological aspects should take into account: certain location regulations, environment monitoring, pro-ecological norms and standards, legal regulations and an efficient control system (cf. E. Gerelli, 1991). Eco-development requires, however, financial means which are a requisite of both scientific progress, necessary to find and apply new technological solutions, and of technological progress making tools and solutions available for new technologies. For these reasons, eco-development in Polish conditions, given the poor financial standing of the state and of local government entities, seems to be a slow process with remote results, yet a process that needs to be started soon and in the fullest extent possible.
Technological determinants of eco-development